SMART HOME AUTOMATIC MENGGUNAKAN MEDIA BLUETOOTH BERBASIS MIKROKONTROLLER ATMEGA 328 - Ageng Setiani Rafika; Meidy Surya Hadi Putra; Winda Larasati (Universitas Raharja, 2015)
The development of technology over time has proven to give a lot of changes in humans. Changes that occur generally for the better, as it easier to do a job One of the technologies developed at this time is with the development of mobile technology is not only used as a telephone and sms only, but also can be used as a device to control a microcontroller. Microcontroller is a chip that can perform digital data processing in accordance with the command given programming language. So today microcontroller applied to many everyday life, one of which is in use in smart home automatic Bluetooth media ATMEGA 328 microcontroller based smart home automatic is a tool that can function automatically based on the input to the bluetooth and the existence of programs that are embedded in in an IC microcontroller. Bluetooth as a communication medium to transmit data or input from android application that is using BlueTerm application that acts as a device to control home appliances remotely. In general, the control of home appliances is still work manually so it is less effective, the objective of the design tool automatic smart home is to create a tool that can help people to carry out activities in the home that is to control the home appliances using smartphones automatically through the application BlueTerm with media bluetooth